The quality of Garut ram liquid semen in Tris egg yolk extender to the sucrose supplementation - Yulnawati .; Herdis . (Indonesian Center for Animal Research and Development (ICARD), 2009)
The successful program of artificial insemination in sheep is determined by the quality of sperm that are used. Therefore, it is important to maintain the quality of sperm during and after storage in low temperature. The research was conducted to study the influence of sucrose in the Tris-yolk extender in maintaining the quality of Garut ram sperm during preservation in reaction tube for four days at 5°C. Ejaculated sperm was collected once a week for five weeks using artificial vagina from same ram. Semen was divided into four groups of extenders, i.e. Tris egg yolk 20% (TKT), TKT + 0,1% sucrose, TKT + 0,3% sucrose and TKT + 0,5% w/v sucrose. The results showed that the percentage of motility on day four (D-4) of storage in TKT (41.00 ± 2.0%) was lower (P<0.05) than that in TKT + 0.3% (48.00 ± 2.45%) and TKT + 0.5% (51.00 ± 3.74%), however there was no significant different (P>0.05) from TKT + 0.1% (45.00 ± 3.16%). Whereas the percentage of live cells (%H) on D-4 in TKT, TKT + 0.1%, TKT + 0.3% and TKT + 0.5% were 55.00 ± 2.19%; 57.20 ± 2.79%; 59.20 ± 3.25% and 61.20 ± 3.60%, respectively. Meanwhile, the percentage of membrane integrity (MPU) in TKT (51.80 ± 1.94%) was significantly different (P<0.05) from TKT + 0.3% (57.40 ± 2.65%) and TKT + 0.5% (59.20 ± 3.66%), however there was no significant different (P>0.05) from TKT + 0.1% (54.80 ± 2.86%). In conclusion, the addition of sucrose 0.3% w/v into TKT extender could maintain the quality of Garut ram sperm more efficiently and better than TKT extender. Key Words: Sucrose, Tris Egg Yolk, Preservation, Garut Sheep